Canonical spectral equation for empirical covariance matrices - Girko, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study asymptotic properties of normalized spectral functions of empirical covariance matrices in the case of a nonnormal population. It is shown that the Stieltjes transforms of such functions satisfy a socalled canonical spectral equation.